Multidrug resistance genes, including blaKPC and blaCTX-M-2, among Klebsiella pneumoniae isolated in Recife, Brazil - Cabral,Adriane Borges (2012)
INTRODUCTION: The prevalence of cephalosporins and carbapenem-resistant Klebsiella pneumoniae strains is rising in Brazil, with potential serious consequences in terms of patients' outcomes and general care. METHODS: This study characterized 24 clinical isolates of K. pneumoniae from two hospitals in Recife, Brazil, through the antimicrobial susceptibility profile, analyses of β-lactamase genes (blaTEM, blaSHV,blaCTX-MblaKPC, blaVIM, blaIMP, and blaSPM), plasmidial profile and ERIC-PCR (Enterobacterial repetitive intergenic consensus-polymerase chain reaction). RESULTS: ERIC-PCR and plasmidial analysis grouped the isolates in 17 and 19 patterns, respectively. Six isolates from one hospital presented the same pattern by ERIC-PCR, indicating clonal dissemination. All isolates presented blaSHV, 62.5% presented blaCTX-M-2, 29% blaTEM, and 41.7% blaKPC. Metallo-β-lactamase genes blaand blawere not detected. Eleven isolates were identified carrying at least 3 β-lactamase studied genes, and 2 isolates carried blaSHVblaTEM, blaCTX-M-2 and blaKPC simultaneously. CONCLUSIONS: The accumulation of resistance genes in some strains, observed in this study, imposes limitations in the therapeutic options available for the treatment of infections caused by K. pneumoniae in Recife, Brazil. These results should alert the Brazilian medical authorities to establish rigorous methods for more efficiently control the dissemination of antimicrobial resistance genes in the hospital environment.